532 nm laser damage and nonlinear absorption of Cr2O72− doped KDP crystals. Issue 8 (15th April 2022) - Zhang, Liyuan; Wang, Shenglai; Li, Tingbin; Yang, Houwen; Cheng, Wenyong; Xu, Longyun; Liu, Hui; Li, Xianglin; Wang, Bo; Xu, Xinguang
Abstract: Potassium dihydrogen phosphate (KDP) single crystals doped with a series of trace dichromate (Cr2 O7 2− ) were prepared using "point seed" technique. The IR spectra suggest that the KDP crystal network becomes compact with trace of Cr2 O7 2− while the lattice of crystal also can be destroyed by excessive doping. The UV–Vis spectra show that the transmittance percentage is descended of the doped KDP crystals. Z-scan analysis demonstrates that with increasing of Cr2 O7 2− concentration, a gradual raise has been observed for the nonlinear absorption coefficient ( β ). The laser-induced damage threshold (LIDT) at 532 nm of the KDP crystal doped with 3000 ppm Cr2 O7 2− is found to be 28.29 J/cm 2 which is higher than that of pure one under the R-on-1 model. However, as the doping concentration continues to increase, the LIDT decreases significantly. The variation of photoluminescence (PL) results is also consisted with the trend of LIDT for the doped samples. The LIDT of pyramidal sample is higher than that of prismatic one with the same doping concentration. The results suggest that the laser damage of doped crystal may be due to a synergistic effect of the concentration of micro defects and nonlinear absorption.